2013
DOI: 10.1002/cjce.21849
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of photo‐Fenton‐like degradation of aqueous polyacrylic acid using Box‐Behnken experimental design

Abstract: The effectiveness of photo-Fenton-like process to degrade aqueous polyacrylic acid (PAA) is investigated in a batch recirculation system using two photoreactors in series. The response surface methodology (RSM) using the Box-Behnken experimental design combined with quadratic programming is employed for the experimental design, the statistical analysis and the optimisation. The effects of the initial concentration of PAA, the initial concentration of H 2 O 2 :Fe 3þ , pH and the recirculation rate on the percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 44 publications
(38 reference statements)
0
23
0
Order By: Relevance
“…The main core of the CCD experimental design is the combination of fractional factorial or factorial and central points.The CCD method was selected to analyze the sensitivity and importance of the parameters selected in this study on the dynamics of particle clouds. Recently, the response surface methodology (RSM) has been used as a reliable tool for model optimization in the field of water and environmental engineering(Ghafoori et al 2014;Kirmizakis et al 2014;and Yahyapour et al 2014) Pakzad et al (2013). used RSM to verify the optimal process design for mixing of a non-Newtonian biopolymer solutions in a reactor equipped with coaxial mixers.…”
mentioning
confidence: 99%
“…The main core of the CCD experimental design is the combination of fractional factorial or factorial and central points.The CCD method was selected to analyze the sensitivity and importance of the parameters selected in this study on the dynamics of particle clouds. Recently, the response surface methodology (RSM) has been used as a reliable tool for model optimization in the field of water and environmental engineering(Ghafoori et al 2014;Kirmizakis et al 2014;and Yahyapour et al 2014) Pakzad et al (2013). used RSM to verify the optimal process design for mixing of a non-Newtonian biopolymer solutions in a reactor equipped with coaxial mixers.…”
mentioning
confidence: 99%
“…in Table 3 and estimated by trial and error, were found to be 1 Â 10 4 and 1 Â 10 2 1/(M s), respectively. [32] R4 [33] R5 [34] R6 10 1/(M s) [35] R7 [35] R8…”
Section: Optimization Of H 2 O 2 Dosage In Uv/h 2 O 2 Processmentioning
confidence: 99%
“…AOPs produce highly reactive intermediates, mainly hydroxyl radicals ( . OH), which are able to oxidize most organics in water . During the UV photolytic process, the UV light with the wavelength energy of more than the bond energy can break the chemical bonds directly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, to analyze processes experimentally, statistical design of experiments is often employed. By utilizing statistical methods, the effect of process variables and their interaction on the experimental output can be quantified; this allows for comprehensive process analysis and optimization (Pakzad et al 2013;Ghafoori et al, 2014;Kirmizakis et al, 2014;Pakzad & Azimi, 2017;Kazemzadeh et al, 2017a).…”
Section: Introduction Objectivesmentioning
confidence: 99%